Causal associations between socioeconomic status and prostate cancer using two-sample Mendelian randomization study - Zhenxing Wang; Chunyan Wang; Xing Gou; Liang Pei; Xiaoyuan Qiao (Scientific Reports)
Abstract Prostate cancer (PCa) is a common form of malignancy among men. The associations between socioeconomic status (SES) indicators and PCa risks remain incompletely elucidated. Through two-sample Mendelian randomization (MR), this research seeks to assess the causal links between 4 genetically predicted SES indicators—average total household income before tax, the Townsend deprivation index at recruitment, unemployed status and college or university degree in the household—and PCa. Genetic variants were extracted from publicly available genome-wide association studies (GWAS) under stringent threshold as instrumental variables (IVs). We employed the inverse variance weighted (IVW), weighted median, weighted mode and MR-Egger to estimate the causal effect, with sensitivity analyses such as Cochran’s Q tests, MR-Egger, MR-PRESSO and leave-one-out performed to detect potential heterogeneity and pleiotropy. Our MR analysis revealed a causal association between unemployment and prostate cancer (OR: 3.07, 95%CI:1.12–8.42, P = 0.03). No causal associations were identified between other SES components and prostate cancer. The MR-PRESSO suggested 2 outliers in the association between college or university degree in household and prostate cancer, which rendered the association significant after outliers were removed. The heterogeneity and pleiotropy are unlikely to affect our causal estimate. Our results indicated that unemployment poses a potential risk factor for the incidence of PCa. The findings highlight the necessity for further exploration into the underlying etiology of PCa.